Hate Speech in the Comments Column of the @dpr_ri Instagram Post Regarding the Post "Statement of Apology and Condolences from the Speaker of the Indonesian House of Representatives" - Novi Imroatul Awaliyah; Aida; Hidhayahten Khasanah; Mintowati (Jurnal Pembelajaran Bahasa dan Sastra, 2025)
This study aims to describe the form of hate speech in the comments column of the Instagram account @dpr_ri on the post of the apology and condolences statement of the Speaker of the Indonesian House of Representatives, Puan Maharani, and explain its legal implications based on Law Number 19 of 2016 concerning Electronic Information and Transactions (UU ITE). This study uses a descriptive qualitative method, and a pragmatic and forensic linguistic approach. The data collection technique uses digital documentation techniques. The data analysis technique uses content analysis techniques combined with pragmatic analysis to reveal the function of expressive speech acts and relate them to the articles of the ITE Law. The results of the study indicate that the hate speech found includes four categories, namely provocation, incitement, insults, and unpleasant actions. Linguistically, the speech contains expressive speech acts with connotations of hatred, while legally it has the potential to violate Article 27 Paragraph (3) concerning insults or defamation and Article 28 Paragraph (2) concerning the spread of hatred based on SARA. The social implications include the erosion of public communication ethics, the emergence of a culture of aggressive speech, and the risk of criminalization due to low digital legal literacy. These findings confirm that pragmatic analysis and forensic linguistics can be used as instruments for early identification of hate speech on social media, while simultaneously strengthening legal awareness and language ethics in Indonesia's digital space.